Upaya Meningkatkan Hasil Belajar SKI Menggunakan Media Gambar Berbasis Karikatur Di MTS Al Muhajirin Langkat - Rahmawati, Fitri (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2025)
This study uses caricature-based visual media at MTs Al-Muhajirin Langkat to promote SKI learning. Caricature-based visuals were chosen because they may help pupils grasp SKI, which has proven tough and monotonous. This qualitative, descriptive study examines how caricature-based visual media is used in SKI education and how it affects student learning. The data was acquired by observation, interviews, and documentation. Caricature-based graphic media makes SKI more approachable and fascinating for students, according to the study. Furthermore, students demonstrated an enhancement in SKI learning outcomes by the utilisation of caricature picture medium dubbed